Aplikasi Tanda Tangan Digital Pada Platform Android - Kristanto, Yoshua Indriasandy; Putra, Putu Bagus Adidyana Anugrah (Journal of Information Technology and Computer Science, 2022)
A signature or initial is a handwriting that is sometimes given a certain style of writing from a person's name or other identification mark. Basically, the signature has a function as written evidence that shows the fulfillment of the terms of the "agreement". Along with the development of digital technology and the emergence of the internet, digital signatures are growing. Now digital signatures are increasingly in demand by the public and are increasingly used by individuals and companies to state institutions for formal purposes involving digital documents. This application was developed using the Extreme Programming methodology. Application development begins with making plans to find the needs of users. Then do the design of the application system that will be made. Followed by design, program implementation and application testing.The results of this study are applications that can create, store, and insert digital signatures in the form of QR Codes or hand drawings into PDF files and save them, and can scan QR Codes either through the camera or take QR Code images from the gallery.